2007
DOI: 10.1002/jso.20664
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in squamous cell carcinomas of the lips and the oral cavity—A single center experience

Abstract: SLNB may contribute to more targeted lymph node dissection strategies. Further studies will have to ensure the safety of this procedure in comparison to selective neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
14
2
1
Order By: Relevance
“…We found 7 SN-positive patients among 45 clinically N0 patients; the upstage rate was 15.6% (7/45). In relevant literature dealing with head and neck mucosal squamous cell carcinoma, it ranges from 8.7 to 40% [6,[13][14][15]. The upstage rate of our study was not very diVerent from those reports.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…We found 7 SN-positive patients among 45 clinically N0 patients; the upstage rate was 15.6% (7/45). In relevant literature dealing with head and neck mucosal squamous cell carcinoma, it ranges from 8.7 to 40% [6,[13][14][15]. The upstage rate of our study was not very diVerent from those reports.…”
Section: Discussioncontrasting
confidence: 69%
“…A falsenegative SN biopsy rate of 7.9% is not very diVerent compared with studies of head and neck cutaneous melanomas and mucosal squamous cell cancers. Those authors reported the false-negative rates of SN biopsy to be 0-10.5% [6,[14][15][16][17][18][19][20][21][22][23][24][25]. We found 7 SN-positive patients among 45 clinically N0 patients; the upstage rate was 15.6% (7/45).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The SNB procedure has shown acceptable sensitivity rates in pilot studies. [11][12][13] In the first multicenter trial for oral and oropharyngeal squamous cell carcinomas, sensitivity was 93% and, therefore, comparable with that of SND.…”
mentioning
confidence: 90%